Capital Market Reaction to Events Before and After the Announcement of Russia’s Invasion of Ukraine: Study on Capital Market of ASEAN Countries - Ariffadin, Salsabila Putri; Sishadiyati, Sishadiyati (Journal of Business Management and Economic Development, 2024)
The purpose of this study is to examine the information content and to determine the capital market reaction of the announcement of the Russian invasion of Ukraine on on February 24, 2022, and to analyze the difference in abnormal returns before and after the announcement of the Russian invasion of Ukraine on the capital markets of ASEAN member countries. This research uses an event study approach and uses the Paired Sample T-Test as a data analysis technique. The population in this study is the capital market of ASEAN member countries with sampling techniques using purposive sampling method. The observation period used is 115 days consisting of 100 days of estimation period and 15 days of event period (7 days before the event, 1 day event date, and 7 days after the event). The results of this study indicate that based on descriptive statistics there are abnormal returns between before and after the event and based on the results of the paired sample t-test there is no difference in abnormal returns before and after the announcement of the Russian invasion of Ukraine.